2017
DOI: 10.3892/or.2017.5505
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of miR-203 increases the sensitivity of NSCLC A549/H460 cell lines to cisplatin by targeting Dickkopf-1

Abstract: The number of new lung cancer cases diagnosed yearly is high, and the mortality rate has not substantially declined. Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, and adenocarcinoma accounts for the largest proportion of NSCLC. Currently, platinum-based combined chemotherapy, particularly cisplatin (DDP) is still the main form of treatment for advanced NSCLC. However, cisplatin resistance often occurs in patients who receive chemotherapy. Previous studies offer various explanations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
7
2
Order By: Relevance
“…In opposition to our results (upregulation in PAC and CIS resistant cell lines), Cheng R. et al showed that, in CIS-resistant NSCLC tumors, miR-203 was downregulated compared with CIS-sensitive tumors [57]. Ectopic expression of miR-203 in the NSCLC cell line increased CIS sensitivity and apoptosis [57]. Overexpression of miR-203 also reversed PAC-resistance in colorectal cancer [58].…”
Section: Discussioncontrasting
confidence: 99%
“…In opposition to our results (upregulation in PAC and CIS resistant cell lines), Cheng R. et al showed that, in CIS-resistant NSCLC tumors, miR-203 was downregulated compared with CIS-sensitive tumors [57]. Ectopic expression of miR-203 in the NSCLC cell line increased CIS sensitivity and apoptosis [57]. Overexpression of miR-203 also reversed PAC-resistance in colorectal cancer [58].…”
Section: Discussioncontrasting
confidence: 99%
“…In opposite to our result (upregulation in PAC and CIS resistant cell lines) Cheng R. et al shown that in CIS-resistant NSCLC tumours miR-203 was downregulated compare with CIS-sensitive tumours [63]. Ectopic expression of miR-203 in NSCLC cell line increases CIS sensitivity and apoptosis [63]. Overexpression of miR-203 also reversed PAC-resistance in colorectal cancer [64].…”
Section: Discussioncontrasting
confidence: 99%
“…Survivin-regulating miR-203 was also suppressed in MPM [75]. In NSCLC cells, miR-203 expression inhibited tumor cell growth, induced apoptosis, and increased the activity of cisplatin by suppression of DKK1 [76]. MiR-345 is highly expressed in malignant mesothelioma samples and its expression may contribute to enhanced cisplatin activity by suppression of the ABC-transporter MRP1, which was associated with multidrug resistance [[77], [78], [79]].…”
Section: Platinum Complexes and Their Interactions With Non-coding Rnmentioning
confidence: 99%